Simulation of cold rolling of bearing rings taking into account the temperature factor - Автономова, Людмила Владимировна; Грозенок, Евгений Денисович (Eastern-European Journal of Enterprise Technologies, 2014)
To ensure the manufacturing accuracy of the bearing rings it is necessary to predict cold rolling process parameters (tool feed rate, forces in the contact area between tool and workpiece, cooling modes, etc.). Therefore, at the process design stage to determine their values, correct mathematical model of the rolling process, which is a related thermoelastoplastic contact problem is needed. The problem of modeling the process of cold rolling of bearing wheels taking into account friction in the contact and influence area of the temperature factor is considered in the paper. Numerical implementation of the 3-dimensional heat conduction problem and the problem of calculating the parameters of thermal stress-strain state of the bearing ring, made of steel SHKH-15 was carried out based on the finite element method using a computer complex DEFORM-3D. Defining relations were set by processing families of deformation diagrams and took into account plastic state of the material in an appropriate range of strain rates and temperatures. Calculations of three-dimensional related contact problem at the two different cooling modes - convective heat transfer with the free air and liquid conducted. The distributions of stress fields, rolling forces and temperature field were obtained. Comparison of the results has shown a significant change in the total force on the tool at different problem statements. Taking into account the temperature factor allows more adequately describe the physical processes in cold rolling of the bearing rings.